2022
DOI: 10.31577/km.2022.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties and cyclic oxidation behavior of Ni-Al-Y superalloys

Abstract: The microstructure, microhardness, and oxidation resistance of ternary model Ni-13Al--2Y (at.%) and Ni-11Al-4Y (at.%) superalloys were studied in detail. The microstructures of alloys consisted of primary γ-Ni dendrites and residual eutectic. The Ni17Y2 intermetallic and γ-Ni were the major constituents of the eutectic phase mixture. The microhardness value of Ni-11Al-4Y alloy was higher than that of Ni-13Al-2Y alloy because of the higher amount of relatively harder eutectic. With increasing Y concentration fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…6. As can be seen, although there are some river lines and smooth facets indicating the appearance of transgranular fractures, the intergranular dominated fracture was observed in the HEA due to the formation of hard and brittle HS phase in the intergrain regions resulting in the weakness of the intergrain regions (27,46). In addition, the formation of tear edges in the fracture surface of the HEA shows relatively ductile behavior of the corresponding regions, which is consistent with what has been found in previous studies (32,47).…”
Section: The Evolution Of Mechanical Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…6. As can be seen, although there are some river lines and smooth facets indicating the appearance of transgranular fractures, the intergranular dominated fracture was observed in the HEA due to the formation of hard and brittle HS phase in the intergrain regions resulting in the weakness of the intergrain regions (27,46). In addition, the formation of tear edges in the fracture surface of the HEA shows relatively ductile behavior of the corresponding regions, which is consistent with what has been found in previous studies (32,47).…”
Section: The Evolution Of Mechanical Propertiesmentioning
confidence: 94%
“…Because of their beneficial effects on molten steel purification and inclusion modification, additions of RE elements into steels have been a popular strategy for tailoring microstructure and improving mechanical performance (24)(25)(26). In addition, Y addition caused a substantial increase in the hardness of Fe-Al and Ni-Al-based superalloys (27,28).…”
Section: Methodsmentioning
confidence: 99%
“…In both specimens, the most advantageous slip system was {110}<111>. Mehmet Sahin Atas et al [13][14][15] studied model Ni-15Al, Ni-Al-Y and Ni-Al-Nb superalloys and showed that aging time significantly influenced the size, shape and type of precipitates in these systems. They also studied these systems ex situ.…”
Section: Introductionmentioning
confidence: 99%
“…However, investigation of the surface scale morphologies does not indicate the entire oxidation process. Internal oxidation can occur under the surface scale[18,20]. Therefore, cross-sectional SEM-EDS analyses (Fig.13) are conducted.…”
mentioning
confidence: 99%